Rancang Bangun Sistem Informasi Akademik Berbasis Web Mobile - Chicie Chandani; Toni Wijanarko Adi Putra; Migunani (Elkom : Jurnal Elektronika dan Komputer, 2020)
Academic means the teaching and learning process carried out in the classroom or school world. Academic information systems at SMAN 1 Ketungau Tengah previously still use manual management systems, such as the calculation of final manual values ​​as a result can cause delays in giving value, the data received is still in the form of paper files that can be lost or damaged, and not connected to the network from one computer to another computer so that the process of moving data still uses a flashdisk. The system certainly has a lot of weaknesses, the implication of which is the weakness of the administrative system, the waste of energy, the less optimal service, for example the distribution of report cards which are sometimes late, slow data processing and calculation errors. The system created aims to help ease calculations, can enter data more effectively and efficiently. The system development method used is SDLC (Sytem Development Life Cycle) which consists of planning, analysis, design, implementation and maintenance. Using the PHP programming language in its creation and MySQL as the database. The results of this study are a Mobile Web-based Academic Information System that helps the admin (staff) in managing data and printing report cards, teachers in managing values, students and parents / guardians in looking at schedules and grades.